The neuroscience of cancer: Focus on neuropeptidergic systems - Zikai Dong; Yongfei Wang; Weilin Jin (Acta Pharmaceutica Sinica B)
Tumors are complex, highly heterogeneous diseases that place an enormous burden on the world's healthcare systems. Updating understanding of tumor initiation and progression is critical and the current breakthrough lies in cancer neuroscience, which focuses on the crosstalk between neural components and tumors. Neuropeptides are a class of highly potent peptides, that perform the physiological functions of neurotransmitters, neuromodulators, and endocrine hormones. Currently, many studies have shown that many cellular components of the tumor microenvironment express neuropeptides and their receptors and that neuropeptides may play an important role in their cellular communication. In addition, neuropeptides and their receptors affect cancer hallmarks such as proliferation, invasion and metastasis, angiogenesis, immune escape, metabolic reprogramming, and others. More importantly, neuropeptides may also affect some tumor comorbidities such as insomnia, depression, anorexia, cancer pain, and others. Targeting neuropeptides in combination with new therapeutic strategies may significantly advance anti-tumor therapy, not only for treating the tumor itself but also for improving the patient's quality of life.